Contested cures : identity and ritual healing in Roman and Late Antique Palestine - Nutzman, Megan S. (Edinburgh studies in religion in antiquity, 2022)
In the ancient Mediterranean world, individuals routinely looked for divine aid to cure physical afflictions. 'Contested Cures' argues that the inevitability of sickness and injury made people willing to experiment with seemingly beneficial techniques, even if they originated in a foreign cultural or religious tradition